KEBIJAKAN PENATAAN PEGAWAI NON PNS OLEH PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI TAHUN 2016-2017 - Darma Yulianda; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Non civil servant staffing in Kuantan Singingi Regency is one of the supporting resources for the implementation of effective and efficient regional government activity. The number of non civil servant staffing in Kuantan Singingi Regency raised by Decree of work agreement by local government has reached 2,949 people in 2016. However, the regional income that tend to decrease in 2016, resulted in the Regional Government of Kuantan Singingi Regency should make arrangements on non civil servant. This policy is carried out by not extending the contracts of all honors workers in 2017 and a moratorium on the appointment of non civil servant staffing. As a result of the local government's policy, various rejection came from non civil servant staffing and the Regional House of Representatives of Kuantan Singingi Regency.The purpose of this study is to describe the Policy of Regulating Non Civil Servant Staffing by Local Government of Kuantan Singingi Regency in 2016-2017 and to know the factors influencing the policy. Next, the research was conducted by using qualitative approaches as well as data collection techniques through interviews, literature study and documentation.The results of this study showed that implementation of staffing arrangements have not run maximally, especially in doing rationalization number of non civil servants staffing. This is because not maximizing the preparation of job analysis which became the basis for knowing the needs of employees in each Organization of Regional Devices. In addition, the government has not been consistent in conducting the moratorium due to the non-employment of non-civil servants in several regional apparatus organizations. The factors that influence the policy of civil servant arrangement non civil servant in Kuantan Singingi regency is the demands of non civil servants and not support the policy of Regional House of Representative.Keywords: Rationalization Policy, Staffing Arrangement, Non Civil Servant